Hypotensive resuscitation in combination with arginine vasopressin may prolong the hypotensive resuscitation time in uncontrolled hemorrhagic shock rats. Issue 4 (April 2015) - Yang, Guangming; Hu, Yi; Peng, Xiaoyong; Zhu, Yu; Zang, Jiatao; Li, Tao; Liu, Liangming
Abstract : BACKGROUND: The optimal resuscitation strategy for traumatic hemorrhagic shock is not completely determined. The objective of the present study was to investigate whether hypotensive resuscitation in combination with arginine vasopressin (AVP) can prolong the hypotensive resuscitation time by minimizing blood loss and stabilizing hemodynamics for uncontrolled hemorrhagic shock. METHODS: With an established rat model of uncontrolled hemorrhagic shock, we compared the beneficial effects of hypotensive resuscitation in combination with AVP to maintain blood pressure at 50 mm Hg for 3 hours to hypotensive resuscitation alone on animal survival, blood loss, and vital organ functions. RESULTS: Hypotensive resuscitation in combination with AVP maintenance for 3 hours significantly reduced total blood loss and fluid requirement during hypotensive resuscitation period and significantly improved the survival of shock rats as compared with hypotensive resuscitation alone. Among the four concentrations of AVP, 5 × 10 −4 U/mL had the best effect: it significantly improved hemodynamics and increased cardiac function, oxygen delivery, as well as hepatic blood flow and hepatic function in the shock rats. However, renal blood flow in the hypotensive resuscitation + AVP group was lower than that in the hypotensive resuscitation alone group. CONCLUSION: Hypotensive resuscitation in combination with early application of AVP could prolong the tolerance time of hypotensive resuscitation and "buy" longer safe prehospital transport time by reducing blood loss and stabilizing hemodynamics. This strategy may be a promising strategy for the early management of trauma patients with active bleeding.